Strategic Effect of Collaboration Between ETICS (2019)
This paper analyzes the relationship between networking capabilities and the motives behind SMEs taking part in collaborative relationships with firms within the same sector. Specifically, we analyzed inter-firm collaborations for new product development and the decision(s) to outsource. The main contribution of this paper is focused on identifying the existence of the mediating effect that Hybrid growth strategy has, connected to these relations. It is argued that the Hybrid growth strategy mediates the relationship between networking capabilities and the different collaborative modes with firms within the same sector. The results, obtained through a binomial logit model, supported these arguments by using a database formed by 450 face-to-face surveys, from which 296 took part in an inter-firm collaboration between 2012-2014. The surveys were given to CEOs from SMEs that participated in collaborative activities with other firms in the Electronic, Technology, Information, and Communications sector (ETICS) in Mexico.